The Role of AI in Scaling Global Access to Quality Education in Low-Resource Regions - Gilang Kartika Hanum; M. Syahputra; Wiwid Suryono; Bernardus Agus Rukiyanto; Slamet Hariyadi (Journal Emerging Technologies in Education, 2024)
Background. In the digital age, emojis have evolved from simple pictographs into a global communication tool, transcending language barriers. As the world seeks to scale access to quality education, particularly in low-resource regions, artificial intelligence (AI) has emerged as a key enabler in overcoming these barriers. The role of emojis in enhancing digital literacy and educational communication in these regions remains underexplored. Purpose. This study investigates the potential of emojis, supported by AI-driven systems, to improve educational accessibility and engagement in low-resource areas. Method. The research aims to explore how AI can leverage emojis as a universal language tool to enhance learning experiences and bridge communication gaps in diverse linguistic and cultural contexts. A mixed-method approach was employed, combining qualitative interviews with educators and students, and quantitative analysis of educational platforms utilizing emoji-based learning interfaces. The study focused on low-resource regions where traditional educational tools are less accessible. Results. Results indicated that emoji-based communication, when integrated with AI-driven educational tools, significantly improved engagement and comprehension among learners, particularly in multilingual environments. Students reported a deeper connection to content and higher motivation to learn, while educators found it easier to communicate complex concepts using visual aids like emojis. The study suggests that AI-supported emoji language can be a scalable solution for improving educational access in underserved regions. Conclusion. In conclusion, the study suggests that adaptive learning algorithms In conclusion, the findings highlight the potential of AI and emojis to revolutionize educational communication in low-resource areas. By leveraging emojis as a universal language, AI can contribute to narrowing the global education gap and fostering inclusive learning.